Hyperspectral multi-indicator ripeness perception model for mechanized harvesting of “Yulu Xiang” pears - Na Ma; Jinyan Sun; Yingjun Li; Shijun Sun; Chenfei Li; Yile Sun; Zonglin Liu; Wendong Niu; Xiaoqin Xue; Haiyan Song (Computers and Electronics in Agriculture, 2026)

Household fuel types and nonfatal cardiovascular diseases in middle-aged and elderly adults - Ruirui Ma; Yingjun Mu; Qingyao Wang; Junyao Huang; Jiayao Zhu; Xudong Wang; Min Zhou; Hui Zuo (Environmental Pollution, 2026)

Cosmetic exposure and hepatic steatosis: Investigating the role of metals and adipokines - Baihao Lin; Hao Deng; Yingjun Wu; Xiang Nie; Xinqi Jiang; Qiuyu Lin; Jiamin Wu; Shengya He; Yonglin Ye; Shuzhen Zhang; Zixiang Luo; Hang Hu; et al. (Food and Chemical Toxicology, 2026)

Unraveling the interactive effects of ammonia, VFAs, and pH on methanogenesis in high-solid anaerobic digestion - Danni Li; Keqiang Zhang; Xingliang Gao; Zhuowu Li; Shenwei Cheng; Siqi Wang; Yingjun Ma; Jingquan Yang; Suli Zhi; Lianzhu Du (Journal of Environmental Chemical Engineering, 2026)

Evolution of single-particle morphology and composition from typical bituminous coal combustion under different temperatures - Junjie Cai; Jun Zeng; Yingjun Chen; Haoran Ma; Hongxing Jiang; Yu Peng; Feiyan Cao; Yong Han; Zeyu Liu; Xinxin Feng (Atmospheric Environment, 2026)

Plasma Tryptophan Hydroxylase 1 Activity-related Metabolic Markers and Stroke Risk: A Nested Case–control Study - Yingjun Mu; Ruirui Ma; Qingyao Wang; Xudong Wang; Shujun Gu; Hui Zuo (Translational Stroke Research, 2026)

Monitoring and analysis of heritage inner surface temperatures using infrared thermal imaging and interpretable machine learning - Duo Zhang; Zengfeng Yan; Pingan Ni; Chaolong Ma; Fan Li; Shanshan Yao; Jiangli Wang; Yingjun Yue; Hanyue Lei; Chenxue Yang; Fuming Lei; Hao Li (Building and Environment, 2026)

Nitrogen and phosphorus recovery by struvite: From fundamental challenges to engineering strategies - Mingye Zhang; Junfeng Liang; Keqiang Zhang; Fuyuan Liu; Xingliang Gao; Zhuowu Li; Yingjun Ma; Xingping Chang; Mengya Wang; Lianzhu Du (Journal of Water Process Engineering, 2026)

Montmorillonite-derived Mg-doped NaAlSiO4 for radiative cooling applications - Zhizheng Xiang; Zhongqiu Tong; Haowei Yang; Jie Yu; Yingjun Xiao; Yueming Wang; Shaoyuan Li; Xingang Li; Mikhail M. Mikhailov; Wenhui Ma (Chemical Engineering Journal, 2025)

Interpretable multi-feature district building energy consumption prediction model: Based on dual attention mechanism and spatiotemporal graph convolutional network - Yingjun Ruan; Yamei Ma; Hua Meng; Tingting Xu; Yuting Yao; Fanyue Qian; Chaoliang Wang; Wei Liu (Energy and Buildings, 2025)

Divergent regulation of nitrogen cycling genes under long-term organic and chemical fertilization in plateau cropland soils - Yingjun Ma; Keqiang Zhang; Shizhou Shen; Huiying Du; Fuyuan Liu; Xingliang Gao; Lianzhu Du; Wenxuan Gao (Applied Soil Ecology, 2025)

Oxygenated aromatic compounds as dominant contributors to the oxidative potential of PM2.5 emitted from biomass burning and coal combustion - Feiyan Cao; Xinxin Feng; Yingjun Chen; Hongxing Jiang; Yong Han; Tian Chen; Yu Shang; Dan Li; Qianyu Zhang; Huimin Ma; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

Traditional and novel organophosphate esters in atmosphere of greenhouse covered with mulch films: Seasonal variations, partitioning and exposure risks - Fang Zhao; Sinuo Tian; Jing Liu; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Hua Ping; Cheng Li (Journal of Hazardous Materials, 2025)

Key toxicity enhancement effect of aqueous-phase secondary formation: Insights from hourly measurements during haze events - Feiyan Cao; Yingjun Chen; Yong Han; Tian Chen; Xinxin Feng; Hongxing Jiang; Qianyu Zhang; Huimin Ma; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

Synergistic hydrogen production and organic pollutant removal via dual-functional photocatalytic systems - Bin Han; Xiangcheng Shan; Hui Xue; Fuyu Liu; Xiaoyang Song; Jiarui Kong; Qiupei Lei; Yingjun Wang; Dongling Ma; Qingzhe Zhang (Journal of Environmental Sciences, 2025)

Moderate grazing intensity with supplemental feeding improves lipid deposition and flavor precursors of lamb revealed by the lipidomics - Huan Yang; Jing Ji; Minle Xu; Xingang Zhao; Zhen Li; Xiuhua Ma; Gaowen Yang; Nan Liu; Yingjun Zhang; Pablo Gregorini; Hailing Luo (Food Bioscience, 2025)

Research on navigation risk assessment index system of intelligent ships - Wenjun Zhang; Xiaoxue Ma; Yingjun Zhang (Ocean Engineering, 2025)

Unveiling the synergy of volatile fatty acids and ammonia nitrogen in optimizing methane production during dry anaerobic digestion of pig manure and corn straw - Zhuowu Li; Danni Li; Shenwei Cheng; Yingjun Ma; Fuyuan Liu; Xingliang Gao; Keqiang Zhang; Rui Liu; Jingquan Yang; Lianzhu Du (Chemical Engineering Journal, 2024)

CuO nano-island anchored Pt catalyst for CO preferential oxidation in H2-rich stream - Xiaomei Zhou; Liang Xu; Ruitong Ma; Yingjun Chen; Qingxin Guan; Wei Li (Chemical Engineering Journal, 2024)

Programmed Cell Death-Related Gene Signature Associated with Prognosis and Immune Infiltration and the Roles of HMOX1 in the Proliferation and Apoptosis were Investigated in Uveal Melanoma - Yubao Zhao; Liang Wang; Xiaoyan Li; Junzhi Jiang; Yan Ma; Shuxia Guo; Jinming Zhou; Yingjun Li (Genes & Genomics, 2024)
Background Uveal melanoma (UVM) is the most common primary ocular malignancy, with a wide range of symptoms and outcomes. The programmed cell death (PCD) plays an important role in tumor development, diagnosis, and prognosis. There is still no research on the relationship between PCD-related genes and UVM. A novel PCD-associated prognostic model is urgently needed to improve treatment strategies. Objective We aim to screen PCD-related prognostic signature and investigate its proliferation ability and apoptosis in UVM cells. Methods The clinical information and RNA-seq data of the UVM patients were collected from the TCGA cohort. All the patients were classified using consensus clustering by the selected PCD-related genes. After univariate Cox regression and PPI network analysis, the prognostic PCD-related genes were then submitted to the LASSO regression analysis to build a prognostic model. The level of immune infiltration of 8-PCD signature in high- and low-risk patients was analyzed using xCell. The prediction on chemotherapy and immunotherapy response in UVM patients was assessed by GDSC and TIDE algorithm. CCK-8, western blot and Annexin V-FITC/PI staining were used to explore the roles of HMOX1 in UVM cells. Results A total of 8-PCD signature was constructed and the risk score of the PCD signature was negatively correlated with the overall survival, indicating strong predictive ability and independent prognostic value. The risk score was positively correlated with CD8 Tcm, CD8 Tem and Th2 cells. Immune cells in high-risk group had poorer overall survival. The drug sensitivity demonstrated that cisplatin might impact the progression of UVM and better immunotherapy responsiveness in the high-risk group. Finally, Overespression HMOX1 (OE-HMOX1) decreased the cell viability and induced apoptosis in UVM cells. Recuse experiment results showed that ferrostatin-1 (fer-1) protected MP65 cells from apoptosis and necrosis caused by OE-HMOX1. Conclusion The PCD signature may have a significant role in the tumor microenvironment, clinicopathological characteristics, prognosis and drug sensitivity. More importantly, HMOX1 depletion greatly induced tumor cell growth and inhibited cell apoptosis and fer-1 protected UVM cells from apoptosis and necrosis induced by OE-HMOX1. This work provides a foundation for effective therapeutic strategy in tumour treatment.

Facet engineering of α-MnO2 for directly electrocatalytic oxygen atom transfer from water toward epoxidation - Yingjun Tian; Baoying Li; Jingrun Wang; Yuyang Ge; Wei Gao; Linyan Yu; Li Ma; Yuehui Li; Ling Wang; Zunqi Liu; Jianbin Chen (Chemical Engineering Journal, 2024)

Occurrence, potential sources, and ecological risks of traditional and novel organophosphate esters in facility agriculture soils: A case study in Beijing, China - Fang Zhao; Hua Ping; Jing Liu; Tianyu Zhao; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

On-board measurements of OC/EC ratio, mixing state, and light absorption of ship-emitted particles - Wenqi Hou; Zeyu Liu; Guangyuan Yu; Shujun Bie; Yan Zhang; Yingjun Chen; Dong Ma; Fan Zhang; Chunjing Lou; Xiaodong Hu; Yong Gui; Weizhong Zhou (Science of The Total Environment, 2023)

Internal exposure risk based on urinary metabolites of PAHs of occupation and non-occupation populations around a non-ferrous metal smelting plant - Bizhi Wu; Meiqing Lin; Hailing Li; Yingjun Wu; Mengdie Qi; Jian Tang; Shengtao Ma; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2023)

Diverse changes in shipping emissions around the Western Pacific ports under the coeffect of the epidemic and fuel oil policy - Yupeng Yuan; Yan Zhang; Jingbo Mao; Guangyuan Yu; Kai Xu; Junri Zhao; Haoqi Qian; Libo Wu; Xin Yang; Yingjun Chen; Weichun Ma (Science of The Total Environment, 2023)

Effects of initial volatile fatty acid concentrations on process characteristics, microbial communities, and metabolic pathways on solid-state anaerobic digestion - Siqi Wang; Danni Li; Keqiang Zhang; Yingjun Ma; Fuyuan Liu; Zhuowu Li; Xingliang Gao; Wenxuan Gao; Lianzhu Du (Bioresource Technology, 2023)

Organic fertilizer substitution over six years improves the productivity of garlic, bacterial diversity, and microbial communities network complexity - Yingjun Ma; Shizhou Shen; Chen Wan; Siqi Wang; Fengxia Yang; Keqiang Zhang; Wenxuan Gao (Applied Soil Ecology, 2023)

Fine mapping and candidate gene analysis of CRA3.7 conferring clubroot resistance in Brassica rapa - Wenxing Pang; Xue Zhang; Yinbo Ma; Yingjun Wang; Zongxiang Zhan; Zhongyun Piao (Theoretical and Applied Genetics, 2022)

The intra-annual intrinsic water use efficiency dynamics based on an improved model - Xiaojin Bing; Keyan Fang; Xiaoying Gong; Wenzhi Wang; Chenxi Xu; Maihe Li; Chaoyue Ruan; Weiting Ma; Yingjun Li; Feifei Zhou (Climatic Change, 2022)

Emergency Situation Safety Evaluation of Marine Ship Collision Accident Based on Extension Cloud Model - Yiyang Zou; Yingjun Zhang; Zhihong Ma (Journal of Marine Science and Engineering, 2021)
After collisions at sea, situation evaluation and analysis are very important to follow-up rescue operations. At present, there are few ways give weights in the current situational safety evaluation methods after collisions of marine ships. Most safety evaluation models ignore the blurred boundaries of evaluation grades. To solve these issues, this paper identifies the safety evaluation indicator system and evaluation standards, and establishes an after-collisions safety evaluation model of maritime ships based on the extension cloud theory. This model combines the extension cloud model, the analytic hierarchy process, the entropy weight method, and game theory. Using this model, the situation safety of two collisions was evaluated. The evaluation results reflect the effectiveness of the model. In order to ensure the safety of the lives and property of marine personnel, suggestions have been made to strengthen crew training, improve ship’s self-rescue ability at sea, and establish a complete marine emergency response rescue system.

Research on Risk Evaluation and Dynamic Escape Path Planning Algorithm Based on Real-Time Spread of Ship Comprehensive Fire - Jian Ji; Zhihao Ma; Jiajun He; Yingjun Xu; Zhiqiang Liu (Journal of Marine Science and Engineering, 2020)
As an independent building entity on the sea, the ship has a large number of internal electrical equipment and a compact space structure, which is prone to fire. This paper proposes a key technology of virtual dynamic escape of ships based on the fire spread prediction model for research. Taking the 63,500 DWT(Dead Weight Tonnage) tanker cabin as a research entity, the mathematical and physical models of ship fire simulation are established. Through the graphical analysis of the experimental data of the fire spread simulation, the temperature, CO concentration, and smoke concentration change rules under different working conditions at the fixed detection point position are obtained. Then, based on temperature, CO concentration and smoke concentration three impact factors, set up a comprehensive fire real-time situational risk evaluation index system. Using the MATLAB software, based on the principle of the fuzzy neural network fire ship’s integrated real-time situational risk evaluation model structure design and simulation test, obtained the corresponding training to comprehensive risk evaluation model of the network. Generate navigation grid according to the law of fire sprawl, and plan escape path. The traditional A* algorithm is improved, and an example is used to prove that the path-finding result after the improved algorithm is shorter than the path found by the traditional algorithm, which meets the path-finding requirements in a three-dimensional environment.

The effect of redox capacity of humic acids on hexachlorobenzene dechlorination during the anaerobic digestion process - Dongyang Li; Beidou Xi; Yingjun Li; Xiaowei Wang; Tianxue Yang; Hong Yu; Caihong Huang; Jianchao Zhu; Qi Li; Xing Peng; Zhifei Ma (Environmental Science and Pollution Research, 2019)

Expression of metallothionein of freshwater crab (Sinopotamon henanense) in Escherichia coli enhances tolerance and accumulation of zinc, copper and cadmium - Yongji He; Wenli Ma; Yingjun Li; Jinping Liu; Weixin Jing; Lan Wang (Ecotoxicology, 2014)